An Examination of Determinants That Affect the Health-Service Systems and Health Status of People in the Greater Mekong Subregion - Ruchiwit; Cowawintaweewat; Pootong; Wareenil; Pawloski (Kashan University of Medical Sciences, 2016)
Background One means of better understanding the variations in health systems among the four greater Mekong subregion (GMS) countries is to determine how the overall health environment influences the area's health-service systems and health status. Objectives The study examined the determinants that affect the health-service systems and health status of the Thai, Lao, Vietnamese, and Cambodian people in the GMS countries, as well as the determinants that best predict health-service-system quality and health status. Patients and Methods The sample groups consisted of 320 - 402 clients and 30 - 69 healthcare providers recruited from three hospitals with similar topographies to those in the respective countries. The sample sizes depended on the number of hospital beds and people in the study areas. The questionnaires included assessments of the perceptions of health-service-system quality and health status, as well as the affecting determinants; the analyses included descriptive statistics, Pearson product-moment correlation, and stepwise multiple regression. Results The major findings included the following: first, for the clients' perceptions, only the internal determinant that reflected the strengths and weaknesses of the hospital environment was shown to be a strong predictor of health-service-system quality of the GMS countries. Second, for both the clients' and providers' perceptions, we found no common determinant that could predict the health status of GMS people, although we did find a few similar and different determinants. Societal and cultural values affected health-service-system quality and the health status of Vietnamese people, as well the health status of the Lao people, while trade and investment only had an impact on the health-status perception of Lao clients. In addition, medical information and technology affected the health-service systems of Thailand and Vietnam, as well as the health status of the people of Thailand and Laos; the living and working environment influenced the health status of the people of Thailand and Vietnam. The strengths and weaknesses of the hospital also affected the health status of the people of Vietnam and Cambodia. Conclusions These findings may be used for further knowledge development and for various practical applications. Our findings recommend that a comprehensive and system-wide review of health-policy planning and strategic settings should be conducted in accordance with those particular factors to improve the health-service systems and health status of the GMS countries.